An investigation into the way in which longitudinal and flexural waves interact with corrosion-like damage - Gonsalez-Bueno, Camila Gianini [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The guarantee of security in transport vehicles, buildings, bridges and critical structures is extremely important for people and the environment. Therefore, in the last decades, several Structural Health Monitoring (SHM) techniques have been proposed and developed for many areas. One technique to detect corrosion could be the use of guided waves. Considering one wave travelling in a structure and impinging on a discontinuity (damage), this wave will interact with this discontinuity and will be scattered. Thus wave motion in structures may be a powerful way to indicate the presence of damage in a structure. This work aims to investigate wave propagation in a thin Euler-Bernoulli infinite beam, and the way in which these waves interact with simulated corrosion damage (symmetric and asymmetric). The studies show the importance to know the behavior of waves before chose main frequencies to used for a SHM system. Piezoelectric elements are used to excite and sense the waves. The behavior of the systems studied are widely discussed in frequency and time domains. In order to detect and quantify the damage, reflected waves showed better sensitivity and proportionality with damage severity for all configuration studied. The longitudinal wave incident in the damage is easier to be used in a SHM system than flexural waves because longitudinal waves present simplicity compared to flexural. However, is important to choose appropriate frequency range in order to generate good levels of the longitudinal waves.

A garantia de segurança em veículos de transporte, edifícios, pontes e estruturas críticas é extremamente importante para as pessoas e o meio ambiente. Portanto, nas últimas décadas, várias técnicas de Monitoramento da Integridade Estrutural (SHM) foram propostas e desenvolvidas para diversas áreas. Uma técnica para detectar corrosão pode ser o uso de ondas guiadas. Considerando uma onda propaganda em uma estrutura e se chocando a uma descontinuidade (dano), esta onda irá interagir com esta descontinuidade e será transformada (parte é refletida e parte transmitida). Assim, o movimento de ondas em estruturas pode ser uma maneira poderosa de indicar a presença de dano em estruturas. Este trabalho tem como objetivo investigar a propagação de ondas em uma viga de Euler-Bernoulli e a forma como estas ondas interagem com danos simulados de corrosão (simétricos e assimétricos). Os estudos mostram a importância de conhecer o comportamento das ondas antes de escolher as freqüências principais a serem usadas em um sistema SHM. Elementos piezelétricos são usados para gerar sensoriar as ondas. O comportamento dos sistemas estudados é amplamente discutido nos domínios de frequência e tempo. Para detectar e quantificar os danos, as ondas refletidas apresentaram melhor sensibilidade e proporcionalidade com a severidade do dano para todas as configurações estudadas. As ondas longitudinais incidentes no dano são mais recomendadas pelo sistema SHM por apresentarem maior simplicidade em relação às ondas de flexural. No entanto, é importante escolher a faixa de frequência apropriada para gerar bons níveis das ondas longitudinais.
Uma investigação sobre a interação de ondas longitudinais e flexurais com danos de corrosão
Keywords: Longitudinal waves; Flexural waves; Piezoelectric elements; Structural health monitoring; Corrosion; Ondas longitudinais; Ondas flexurais; Elementos piezelétricos; Monitoramento da integridade estrutural; Corrosão